Answers

2016-03-21T22:45:40+05:30
Let the age of father be x years and sum of the ages of two children be y years . According to question: Father's age is three times the sum of his two children. ⇒x=3y ........(1) After 5 years - Father's age = (x+5) years Sum of the ages of two children = (y+5+5) years = (y+10) years According to question: ⇒(x+5)=2(y+10) Putting x = 3y from (1) to (2),we get: ⇒3y+5=2y+20 ⇒3y−2y=20−5 ⇒y=15 Putting y = 15 in (1),we get ⇒x=3×15 ⇒x=45 Thus,the age of father = 45 years
0